Multicomponent bulk metallic glasses with elevated-temperature resistance. (November 2019) - Inoue, A.; Kong, F.L.; Zhu, S.L.; Greer, A.L.
Abstract: Abstract : Metallic glasses have attractive properties, but since the glassy state is inherently metastable, they are not normally considered for applications at elevated temperatures. Yet, studies have shown that multicomponent and pseudo high-entropy (PHE) compositions can confer useful heat resistance. The formation, thermal stability, and mechanical and chemical properties of multicomponent Fe-(Cr, Mo)- and Zr-based bulk metallic glasses (BMGs) are reviewed to assess their potential as heat-resistant structural materials. The composition Fe43 Cr16 Mo16 C15 B10 is castable and fully glassy with rod diameters up to 2.7 mm. Glassy coatings of this material with low porosity, good mechanical properties, and good corrosion resistance can be produced by high-velocity spray coating. The compositions Zr55–65 Al7.5–10 (TM1, TM2 )27.5–35 (TM1 = Fe, Co, Ni, TM2 = Cu, Pd, Ag, Au) yield PHE BMGs, in which a stable cluster-like glassy phase without crystalline precipitates is formed by annealing at temperatures well above the first calorimetric transformation. It is suggested that proliferation of alloy components is an effective method to synthesize metastable metallic materials that retain high strength at elevated temperatures.